Studying the Mechanical Properties of Denture Base Materials Fabricated from Polymer Composite Materials - Oleiwi, Jawad Kadhim; Hamad, Qahtan Adnan (Al-Khwarizmi Engineering Journal, 2018)
In this research, the effect of adding two different types of reinforcing particles was investigated, which included: nano-zirconia (nano-ZrO2) particles and micro-lignin particles that were added with different volume fractions of 0.5%, 1%, 1.5% and 2% on the mechanical properties of polymer composite materials. They were prepared in this research, as a complete prosthesis and partial denture base materials was prepared, by using cold cure poly methyl methacrylate (PMMA) resin matrix. The composite specimens in this research consist of two groups according to the types of reinforced particles, were prepared by using casting methods, type (Hand Lay-Up) method. The first group consists of PMMA resin reinforced by (nano-ZrO2) particles, while the second group consists of PMMA resin reinforced by (micro-lignin) particles.The mechanical tests performed in this research includedtensile test, compression test, impact test and hardness test. The results of this study showed that the values of tensile modulus of elasticity, compressive strength and hardness properties increased with increasing the volume fraction of these particles in PMMA composite materials. While, the values of tensile strength, elongation and impact strength properties decreased. Also, the addition of (nano-ZrO2) particles showed greater effect than that of (micro-lignin) particles in some properties of PMMA composite materials for prosthesis denture base materials specimens, while they have lower effect for the other properties.